2019
DOI: 10.1210/jc.2019-00672
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Asian Haplotype of KCNJ18 to Susceptibility to and Ethnic Differences in Thyrotoxic Periodic Paralysis

Abstract: Context and Objectives Thyrotoxic periodic paralysis (TPP) is an acute complication of thyrotoxicosis that can be lethal. TPP is rare in Caucasians but often affects young men in East Asian populations. This study aimed to clarify the contribution of KCNJ18 to susceptibility to TPP in East Asian populations. Participants and Methods The study comprised 635 participants including 13 Japanese patients with TPP, 208 Japanese pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…The KCNJ18 gene (potassium inwardly rectifying channel subfamily J member 18) encodes the inwardly rectifying potassium channel, Kir2.6. The locus is regulated by thyroid hormone, and variants in KCNJ18 have been associated with TPP [ 4 , 7 , 10 , 15 ]. A major haplotype of KCNJ18 in East Asian populations is significantly associated with susceptibility to TPP, and this haplotype is much more common in East Asian than Caucasian populations [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The KCNJ18 gene (potassium inwardly rectifying channel subfamily J member 18) encodes the inwardly rectifying potassium channel, Kir2.6. The locus is regulated by thyroid hormone, and variants in KCNJ18 have been associated with TPP [ 4 , 7 , 10 , 15 ]. A major haplotype of KCNJ18 in East Asian populations is significantly associated with susceptibility to TPP, and this haplotype is much more common in East Asian than Caucasian populations [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although earlier findings had suggested Hashimoto’s thyroiditis is more common amongst White populations ( 213 ), more recent research suggests Japanese and Korean Graves’ disease patients are at greater risk of disease complications when compared to Caucasian people ( 214 ). In addition, a study in a South African cohort has shown White populations to be at higher risk of developing myasthenia gravis.…”
Section: Epidemiological Factors Affecting the Prevalence Of Ocular Complication With Autoimmune Disordersmentioning
confidence: 97%
“…Obwohl frühere Befunde darauf hindeuteten, dass die Hashimoto-Thyreoiditis in der weißen Bevölkerung häufiger vorkommt [213], deuten neuere Untersuchungen darauf hin, dass japanische und koreanische Patienten mit Morbus Basedow ein höheres Risiko für Krankheitskomplikationen haben als kaukasische Menschen [214]. Darüber hinaus hat eine Studie in einer südafrikanischen Kohorte gezeigt, dass weiße Bevölkerungsgruppen ein höheres Risiko haben, an Myasthenia gravis zu erkranken.…”
Section: Epidemiologische Faktoren Die Die Prävalenz Von Augenkomplik...unclassified